1993
DOI: 10.1149/1.2220736
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Submicron Ammonium Sulfate Particles on the Corrosion of Copper

Abstract: The effect of submicron-sized (NH4)2SQ particles on the corrosion of copper has been investigated in air-H20 mixtures at 373 K and relative humidities (RH) of 65, 75, and 88%. At 65% RH, (NH~)2SO4 particles do not affect the oxidation of copper. At 75 % RH, the "critical relative humidity" of (NH4)2SO4, localized formation of Cu20 and a basic copper sulfate, brochantite [Cu4(SO4)(OH)6] or antlerite [Cu~(SO~)(OH)4], isobserved, depending on the amount of particles deposited. At 88% RH, sufficient water is absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 4 publications
(11 reference statements)
3
22
0
Order By: Relevance
“…R ct , representing the difficulty of charge transfer, could give some information about the corrosion resistance. The R ct of copper sample after 7 days of immersion is the highest one among these samples, which is consistent with the corrosion current extrapolated by polarization curves in Copper immersed in (NH 4 ) 2 SO 4 solution usually undergoes anodic dissolution to generate Cu + ions, [1,[13][14][15][16] which will react with ammonia derived from the hydrolysis of ammonium ions to generate [Cu(NH 3 ) n ] + . However, Cu + and [Cu(NH 3 ) n ] + ions can be rapidly oxidized to Cu 2+ and [Cu(NH 3 ) n ] 2+ ions under aerobic conditions.…”
Section: Eissupporting
confidence: 81%
See 2 more Smart Citations
“…R ct , representing the difficulty of charge transfer, could give some information about the corrosion resistance. The R ct of copper sample after 7 days of immersion is the highest one among these samples, which is consistent with the corrosion current extrapolated by polarization curves in Copper immersed in (NH 4 ) 2 SO 4 solution usually undergoes anodic dissolution to generate Cu + ions, [1,[13][14][15][16] which will react with ammonia derived from the hydrolysis of ammonium ions to generate [Cu(NH 3 ) n ] + . However, Cu + and [Cu(NH 3 ) n ] + ions can be rapidly oxidized to Cu 2+ and [Cu(NH 3 ) n ] 2+ ions under aerobic conditions.…”
Section: Eissupporting
confidence: 81%
“…One of the common salt particles within the rural and industrial atmosphere is (NH 4 ) 2 SO 4 , which would be dissolved to form a thin (NH 4 ) 2 SO 4 solution layer on copper surface when the ambient humidity gets greater than the critical relative humidity of (NH 4 ) 2 SO 4 and consequently gives rise to the corrosion of copper. [1,[13][14][15][16] Especially, haze is very serious in winter in northern China, and (NH 4 ) 2 SO 4 is one of the main pollutants in haze, which causes serious corrosion of metallic materials. [17,18] It was reported that the corrosion behavior is quite similar to that in the bulky (NH 4 ) 2 SO 4 solution when the electrolyte film thickness on the metal surface reaches 20-30 molecular layer thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic copper chloride and carbonate are also found [180][181][182][183][184]. The mechanism of basic copper sulfate formation has been the subject of several studies that have been reviewed [183,184].…”
Section: Atmospheric Corrosionmentioning
confidence: 99%
“…The effect of submicron (NH 4 ) 2 SO 4 particles on the corrosion of copper at varying relative humidities (RHs) and-temperatures was studied by Lobnig et al [180,181], who showed that (NH 4 ) 2 SO 4 particles lead to the corrosion products found in natural patinas. In a recent study [189], it was investigated whether NH 4 HSO 4 and (NH 4 ) 3 H(SO 4 ) 2 may be responsible for formation of basic copper sulfate in the naturally formed patina on copper during atmospheric corrosion.…”
Section: Atmospheric Corrosionmentioning
confidence: 99%